Introduction to Sociocybernetics (Part 3): Fourth order cybernetics - Mancilla, Roberto Gustavo (Journal of Sociocybernetics, 2014)
The purpose of this paper is to complement those that have preceded, changing the focus from the dynamics of social systems to that of individual human systems. It will be seen that fourth order cybernetic systems study self-observing systems, which are comprised by cognitive machines, information processing mechanisms that reside in the human mind. Of these, the one of rationality will be explored and then related to that of language, which acts as cognitive bridge between human systems. A model of rationality as though coherence will be offered to the reader, it will be contrasted with the traditional notion of rationality as means ends analysis, which is found in economics and philosophy.